Crime and Criminal Justice in Modern Germany - Richard F. Wetzell (Berghahn Books, 2014)
Historians of nineteenth- and twentieth-century Germany have been relative latecomers to the history of crime and criminal justice. In both modern British and French historiography, crime and criminal justice have been major topics of research since the 1970s: in France, research in this area was pioneered by Michel Foucault, in Britain, by E. P. Thompson and other social historians.1 In the field of German history, the significance of this subject was first recognized by historians of the early modern era, who developed a rich literature on this topic over the last twenty-five years.2 Historical research on crime and criminal justice in nineteenth- and twentieth-century Germany, by contrast, has only begun to flourish in the last ten years. It is the aim of this volume to make some of the results of this recent boom in research accessible to a general audience. There is a notable asymmetry between the early modern and modern German historiographies of crime and criminal justice. Whereas most early modern studies have focused on the criminals themselves, their socioeconomic situations, and the meanings of crime in a particular urban or rural milieu, late modern studies have tended to focus on penal institutions and the discourses of prison reformers, criminal law reformers, criminologists, and psychiatrists. Simplifying somewhat, one might say that early modernists have studied crime and criminal justice primarily with the tools of social history and historical anthropology, while late modernists have most often used the tools of cultural history, intellectual history, and discourse analysis.3 To some extent, this difference in approaches reflects the effect that the â€œscientization of the socialâ€ began to have on criminal justice in the last third of the nineteenth century.4 Compared with what we know about the early modern era, our knowledge of the history of crime and criminal justice in the various German states in the first two-thirds of the nineteenth century is very limited. Although we are beginning to learn more about the important transformations of criminal justice that took place in this period,5 most late modern research on crime and criminal justice picks up after the German unification of 1871, a fact that is reflected in this collection.